Analysis of Students' Profile Using Four Tier Test Instrument on Temperature, Heat, and Thermal Expansion Topics in Junior High School - Putri, Niken Dwi; Arif*, Khairil; Oktavia, Rani; Afrizon, Renol (Jurnal IPA & Pembelajaran IPA, 2025)
Misconceptions are erroneous understandings of concepts that tend to persist and are difficult to change, hindering learning processes and affecting student learning outcomes. In science education, misconceptions frequently occur in highly complex concepts, particularly in temperature, heat, and thermal expansion topics. This occurs because these concepts are abstract and everyday phenomena do not always align with scientific concepts. Therefore, identifying and analyzing student misconceptions becomes crucial. This study aims to analyze students' misconception profiles on temperature, heat, and thermal expansion topics using four tier test instruments. This research employed descriptive quantitative methods with a population of all grade VII advanced students from A-accredited junior high schools in West Padang Panjang District during the second semester of 2025/2026 academic year. The sampling technique used total sampling. The research sample consisted of grade VII advanced students from three schools: SMPN 1, SMPN 2, and SMPN 4 Padang Panjang. The research instrument comprised 19 four tier test questions with four levels: concept answers, answer confidence levels, reasoning for answer selection, and reasoning confidence levels. Results showed an average percentage of students experiencing misconceptions at 24% with low category. The misconception profile revealed two indicators in moderate category: explaining temperature concepts (31.5%) and determining factors affecting heat (32%), while nine other indicators were in low category ranging from 13%-29%. Identified misconception types included false positive, false negative, and pure misconceptions